THE ROLE OF WOMEN IN THE MODERN SOCIETY - Mamadjonova, Sevara (INTERNATIONAL CONFERENCES, 2023)
This article shows women’s purposes, dreams, intentions toward life, although they have got barriers in the society. Also, women rights, their positions in real life and main improvements will be mentioned in this article.